Advances in Neural Networks - ISNN 2009 6th International Symposium on Neural Networks, ISNN 2009 Wuhan, China, May 26-29, 2009 Proceedings, Part II - Yu, Wen; He, Haibo; Zhang, Nian (Theoretical Computer Science and General Issues,, 2009)
The three volume set LNCS 5551/5552/5553 constitutes the refereed proceedings of the 6th International Symposium on Neural Networks, ISNN 2009, held in Wuhan, China in May 2009. The 409 revised papers presented were carefully reviewed and selected from a total of 1.235 submissions. The papers are organized in 20 topical sections on theoretical analysis, stability, time-delay neural networks, machine learning, neural modeling, decision making systems, fuzzy systems and fuzzy neural networks, support vector machines and kernel methods, genetic algorithms, clustering and classification, pattern recognition, intelligent control, optimization, robotics, image processing, signal processing, biomedical applications, fault diagnosis, telecommunication, sensor network and transportation systems, as well as applications.